Longitudinal changes in the prevalence of adult asthma: An epidemiological survey among Japanese salaried employees and their dependents using healthcare insurance claim from 1999 to 2019 - Kisako Nagayama; Yuma Fukutomi; Eiji Nakatani; Yuto Hamada; Mari Irie; Kazuhiro Azekawa; Yasuhiro Tomita; Kentaro Watai; Yosuke Kamide; Kiyoshi Sekiya; Yoichi Nakamura; Chiharu Okada; et al. (Allergology International, 2023)
Background: Information on changes in asthma prevalence and the treatment status for asthma is used as basic information for taking medical and administrative measures against asthma. However, this information among adults is relatively limited. Methods: To elucidate changes in the prevalence of asthma and treatment status over time among Japanese adults, health insurance claim data from some health insurance societies covering salaried employees and their dependents were studied longitudinally. Claim data from FY1999 to 2007 were obtained from two health insurance societies, and data from FY 2011 to 2019 were obtained from three different health insurance societies, and changes in standardized asthma prevalence among subjects aged 20–59 years, proportion of asthma patients prescribed ICS, leukotriene receptor antagonist (LTRA), and LABA, and the mean number of acute asthma exacerbations per year were analyzed. Results: The prevalence of asthma increased from 1.6% in 1999 to 3.0% in 2007 and 2.9% in 2011 to 4.6% in 2019. Increased trends in asthma prevalence from 2011 to 2019 were more noticeable in subjects in their 50s than those in their 20s for both sexes. The number of emergency visits related to asthma was 1.5 per year in 1999, which decreased to 0.8 per year in 2019. The proportion of people prescribed all anti-asthma medications (ICS, LTRA, and LABA) increased over time. Conclusions: The prevalence of adult asthma among Japanese salaried employees and their dependents has increased over the last 20 years, suggesting more attention should be paid to the prevention of this disease in adults.